Publikacja aktu prawnego. Uwagi de lege lata i postulaty de lege ferenda - Kurek, Justyna (Kwartalnik Prawa Publicznego, 2012)
Information regarding binding legislation and applicable law is crucial for all legal entities. Neither, provisions about publication of normative acts, nor publicly available, free of charge databases with legal information guarantee access to consolidated legal acts. The aim of this paper is to prove how new regulations concerning re-use of public sector information may stimulate access to legal information.